1987
DOI: 10.1116/1.574258
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectric calorimeter for photothermal studies of thin films and adsorbates

Abstract: A pyroelectric calorimeter for studies of radiation induced thermal transients in thin films and at surfaces is described. The signal generation and detection process, as well as design criteria are briefly reviewed. Detailed data are presented whereby our design, which has found extensive utility, can be fabricated. This device is compatible with standard Inficon quartz microbalance hardware and provides a sensitivity of several nanojoules at a time resolution of <100 ns over a wide temperature and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Here, the pyroelectric parameters have been assumed homogeneous and temperature independent as normally justified under ordinary experimental conditions. 41 Therefore, a current…”
Section: B Theory Of the Photopyroelectric Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the pyroelectric parameters have been assumed homogeneous and temperature independent as normally justified under ordinary experimental conditions. 41 Therefore, a current…”
Section: B Theory Of the Photopyroelectric Effectmentioning
confidence: 99%
“…Moreover, such materials must be characterized also by a relatively large value of the Curie temperature. 41 In fact, operation of detectors sufficiently below such a temperature implies a very weak temperature dependence of the pyroelectric coefficient, which is advisable when performing measurements as a function of temperature as in case of investigations over phase transitions. Among others, lithium tantalate (LaTiO 3 ) is one of the most commonly adopted pyroelectric material due its relatively large figure of merit (∼15) and high value of the Curie temperature (∼600 • C).…”
Section: A Background On Pyroelctric Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, regularization was also used by Wubbenhorst and Wiinsche and Bloss et al [115,116]. Physical insight into the reason for a nonuniform resolution was gained by Leal-Ferreira [ l l v and Coufal et al [118], who proposed scaling transformations in order to obtain an approximation of the desired charge or polarization profiles. These ideas were further developed by Ploss et al [119], and by Bauer [120].…”
Section: Pyroelectric Depthmentioning
confidence: 99%
“…Polarization gradients were observed near the electrode-coated surfaces. Investigations of these depolarized near-surface layers were reported by Coufal et al [118] and by DeReggi and Broadhurst [lo81 who used the thermal-pulse technique, as well as by Ploss et al [119] and Ploss and Bianzano [129], who employed the thermal wave techmque. It was found that with increasing film thickness, the homogeneity of the polarization decreased [118].…”
mentioning
confidence: 99%